2019
DOI: 10.1590/0102-311x00098918
|View full text |Cite
|
Sign up to set email alerts
|

Acurácia da determinação da idade gestacional no Sistema de Informações sobre Nascidos Vivos (SINASC): um estudo de base populacional

Abstract: Resumo: A prevalência de nascimento pré-termo tem apresentado uma tendência crescente em vários países, inclusive naqueles desenvolvidos. Estudos no Brasil relatam que o Sistema de Informações sobre Nascidos Vivos (SINASC), até 2010, subestimava a prevalência de nascimentos pré-termo, quando comparada aos estudos baseados em dados primários. A partir de 2011, a idade gestacional ao nascer no SINASC tem sido calculada, quando disponível, pela data da última menstruação (DUM). O objetivo foi avaliar a acurácia d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
7
Order By: Relevance
“…With respect to ethnicity, despite having exclusive options, the 2012-2015 databases presented values associated with marital status in this field. Data related to inaccuracies in this variable were not found in studies; nonetheless, incompleteness, such as the ignored option, was identified in national research following the gradual implementation of the new DNV form in 2011, when the variable was introduced 16 . In another analysis, ethnicity was classified as poor in most cities, particularly in São Luís, where incompleteness reached 36.8% 12 .…”
Section: Discussionmentioning
confidence: 99%
“…With respect to ethnicity, despite having exclusive options, the 2012-2015 databases presented values associated with marital status in this field. Data related to inaccuracies in this variable were not found in studies; nonetheless, incompleteness, such as the ignored option, was identified in national research following the gradual implementation of the new DNV form in 2011, when the variable was introduced 16 . In another analysis, ethnicity was classified as poor in most cities, particularly in São Luís, where incompleteness reached 36.8% 12 .…”
Section: Discussionmentioning
confidence: 99%
“…A omissão da idade gestacional deve ser motivo de preocupação, dada sua importância como indicador de saúde do recém-nascido. Nascimentos prematuros geram demandas adicionais sobre os serviços de saúde de alta complexidade, e suas complicações relacionamse a desfechos desfavoráveis na morbidade e mortalidade a curto e longo prazo 22,23 . Nesse sentido, alerta-se sobre a tendência crescente na prevalência de nascimento pré-termo no Brasil, assim como em vários países 23 .…”
Section: Discussionunclassified
“…Gestational age was linked to the health certificate records at birth instead of using the date of last menstruation because the latter overestimates the weight higher than or equal to 2,500g in preterm birth, considering lower gestational age. 13 Maternal pre-gestational nutritional status of the woman was operationalized with the body mass index (BMI) before pregnancy [weight (kg) / height (m) 2 ], which was categorized into four groups: low weight (< 18.5 kg/m 2 ), normal weight (18.5 -24.9 kg/m 2 ), overweight (25.0-29.9 kg/m 2 ) and obesity (≥30.0 kg/m 2 ). 14 Pregnancy controls were classified as adequate, intermediate, and inadequate, using a measure of the required number of visits according to the weeks of gestation, where the higher gestational age requires a higher number of prenatal care visits.…”
Section: Methodsmentioning
confidence: 99%